Multiple lymphoid nodules in bone marrow biopsy in immunocompetent patient with cytomegalovirus infection: an immunohistochemical analysis - Magalhães,Silvia Maria Meire (2001)
In Brazil, a high prevalence of cytomegalovirus (CMV) infection has been documented. In immunocompetent adults CMV infection is usually asymptomatic and therefore morphologic and immunophenotypic bone marrow changes have rarely been described. The authors report the case of a previously healthy patient who developed fever of undetermined origin. The diagnosis of acute CMV infection was based on serological testing. A computed tomographic scan showed mediastinal lymphadenopathy. A bone marrow biopsy revealed a hypercellular haematopoiesis with eosinophilia and large mixed T- and B-cell lymphoid aggregates. In spite of bcl-2 positivity, their reactive nature was demonstrated. Polymerase chain reaction (PCR) and immunohistochemistry were unable to detect CMV-DNA in paraffin-embedded bone marrow sections. Much like in other systemic disorders, the lymphoid nodules in this case seemed to be caused by immunological mechanisms, possibly due to cytokines released in response to the systemic infectious process.